Ecotourism: Local Community's Role in Overcoming Watershed Pollution in Lake Cisanti, West Java - Anwar, Rully Khairul; Khadijah, Ute Lies Siti (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2024)
The World Bank said that the Citarum River was the most polluted river in the world, which led to safety measures and practical solutions. At the same time, this problem opens up opportunities for ecotourism, but it depends on how involved the people of the Citarum River are. A study looks at the roles that people from Tarumajaya village played in the planning, implementation, and evaluation phases of Lake Cisanti ecotourism. The research is based on a case study of Tarumajaya village, Kertasari sub-district, Bandung Regency, and Lake Cisanti's location. Interviews, non-participant observations, and documentation studies are all ways to collect data. There are three kinds of participation: planning, putting things into action (like protecting the environment and doing other things), and evaluating. This study shows how community involvement could help clean up rivers, restore nature, and make ecotourism stronger. Contribution: The research emphasizes the critical roles that local residents play in all phases of ecotourism development—planning, implementation, and evaluation. This underscores the importance of community engagement in environmental management efforts.